Linguistic Competency Profile of Elementary School Students: Vocabulary, Reading and Writing Skills Analysis - M. Isnaini; Hidayah Budi Qur'ani (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2023)
Linguistic competence is a fundamental foundation in the development of the academic abilities of elementary school students. This study aims to analyze the linguistic competency profile of elementary school students through a study of vocabulary, reading skills, and writing using the Systematic Literature Review (SLR) approach. The research method uses the PRISMA Model by searching literature from the Scopus database, Google Scholar, Garuda Portal, and ERIC for the period 2014-2024. The inclusion criteria include empirical research that focuses on elementary school students with at least one component of linguistic competence. Data analysis uses thematic synthesis to identify patterns and themes in the literature. The results showed that the vocabulary of elementary school students was dominated by nouns (37%) and verbs (35%) with the root word (62%) as the main form, reflecting the mastery of concrete concepts. Reading proficiency showed that 39.6% of students were not fluent in reading, while writing proficiency showed the greatest challenge with 65.2% of students not mastering writing skills. There was a strong correlation (rxy = 0.993) between linguistic intelligence and reading ability. Influencing factors include individual, social, cultural, and pedagogical aspects. This study confirms that linguistic competence is an integrated multidimensional construct, requiring a holistic, contextual, and transformative learning approach. The findings provide important implications for the development of integrated curriculum, learning strategies, and assessment systems to improve the quality of literacy in primary schools.